Effects of Fiscal Stimulus in Structural Models - Coenen, Günter; Erceg, Christopher J.; Freedman, Charles; Furceri, Davide; Kumhof, Michael; Lalonde, René; Laxton, Douglas; Lindé, Jesper; Mourougane, Annabelle; Muir, Dirk; Mursula, Susanna; De Resende, Carlos; et al. (American economic journal. Macroeconomics, 2012)
The paper subjects seven structural DSGE models, all used heavily by policymaking institutions, to discretionary fiscal stimulus shocks using seven different fiscal instruments, and compares the results to those of two prominent academic DSGE models. There is considerable agreement across models on both the absolute and relative sizes of different types of fiscal multipliers. The size of many multipliers is large, particularly for spending and targeted transfers. Fiscal policy is most effective if it has moderate persistence and if monetary policy is accommodative. Permanently higher spending or deficits imply significantly lower initial multipliers.